2018
DOI: 10.1093/jncics/pky076
|View full text |Cite
|
Sign up to set email alerts
|

Who Will Benefit From Expanding HPV Vaccination Programs to Boys?

Abstract: Indications for human papillomavirus vaccination programs are expanding to boys. However, the rationale behind their inclusion is often not clear. Using a Bayesian synthesis framework and assuming equal vaccine coverage in both sexes, we assessed how the incremental number of cancer cases prevented and life-years gained from boys’ vaccination are distributed between women, heterosexual men, and men who have sex with men (MSM). Below 60% coverage, at least 50% of the gains from boys’ vaccination was attributabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The authors recognize that this is a simple iteration but it is still based on real models. They consider that the most important effect of this vaccination is the herd effect (34).…”
Section: Results Of the Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recognize that this is a simple iteration but it is still based on real models. They consider that the most important effect of this vaccination is the herd effect (34).…”
Section: Results Of the Individual Studiesmentioning
confidence: 99%
“…This information can be of use in order to extend and support the male vaccination program. It is an important program because these changes may be entirely new, if the program targets both sexes or females and MSM (34).…”
Section: Results Of the Individual Studiesmentioning
confidence: 99%
“…Nevertheless, other authors claim that a program for MSM will not be able to target MSM before their sexual debut, or in fact even shortly after sexual debut because most MSM only disclose their sexual preference to health care providers in their early 20's 29 . Qendri et al 30 have also studied the benefits of sex‐neutral vaccination using a Bayesian framework, and they have found that the extra protection gained by women (apart from the direct protection of MSM) could provide a reason to vaccinate also boys.…”
Section: Discussionmentioning
confidence: 99%
“…Female-only HPV vaccination programs have several shortcomings ( 25 ) including the consideration of only cervical cancer as a HPV transmission outcome ( 21 ) and multiple additional assumptions: (1) of monogamy or serial monogamy with few lifetime partners without the consideration of polygamous societies ( 20 ); (2) of heterosexual relationships, thus discounting the potential for HPV spread through bisexual contact and by way of men who have sex with men ( 26 ); (3) of penile-vaginal intercourse, thus minimizing the consideration of digital and oral spread of HPV; (4) of the presence of gender equity without consideration of women's structural barriers (such as lack of autonomy, early marriages, and lack of education); and (5) of a uniform geographic and other social determinant acceptability of HPV vaccination. These assumptions may contribute to inequities as well as mistrust and misinformation.…”
Section: Introductionmentioning
confidence: 99%